Data and derived products from airborne radar sounding survey over Devon Ice Cap, Canadian Arctic - Anja Rutishauser; Donald D. Blankenship; Duncan A. Young; Natalie S. Wolfenbarger; Lucas H. Beem; Mark L. Skidmore; Ashley Dubnick; Alison S. Criscitiello; Dillon P. Buhl; Thomas G. Richter; Gregory Ng (Zenodo, 2021)
Data and derived products used in Rutishauser et al., “Radar sounding survey over Devon Ice Cap indicates the potential for a diverse hypersaline subglacial hydrological environment”, accepted for publication, The Cryosphere, https://doi.org/10.5194/tc-2021-220 Corresponding author: rutishauser.anja@gmail.com Description of datasets: --- 2018_DIC_UTIG.IR2HI1B.kml Geolocation of the SRH1 profile lines. Coordinates in EPSG: 4326 - WGS 84 (latitude, longitude) --- 2018_DIC_UTIG.IR2HI1B.tgz HiCARS 2 L1B echo strength profiles (radargrams) in NetCDF format. The naming of the files has the structure IR2HI1B_YYYYDOY_PST_x (e.g. IR2HI1B_2018153_DEV_JKB2t_Y87b_000.nc), where YYYY is the survey year (e.g. 2018), DOY is the survey day of the year (e.g. 153), PST is the profile name (e.g. DEV_JKB2t_Y87b), and x is the segment number if the profile was split in two (e.g. 000). For each profile, a PDF file showing the profile location and the radargram is included. --- 2018_DIC_UTIG.Level2.tgz Level 2 datasets for each profile, organized in the following folders: 2018_DIC_UTIG.ILUTP2: Laser altimeter geolocated surface elevation 2018_DIC_UTIG.IR2HI2: HiCARS 2 unfocused (pik1) geolocated ice thickness, ice surface elevation, bed elevation, surface- and bed reflection coefficients, and aircraft roll 2018_DIC_UTIG.IRHFOC2: HiCARS 2 focused (foc1) geolocated ice thickness, ice surface elevation, bed elevation, surface- and bed reflection coefficients, and aircraft roll 2018_DIC_UTIG.IRSPC2: HiCARS 2 derived basal interface specularity content --- Devon_basal_ice_temperature.tif: Modeled basal ice temperature [ºC] using a 1D advection diffusion model. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. --- Devon_bedrockDEM.tif: Digital elevation model (DEM) of the bedrock topography beneath Devon Ice Cap [m asl.].500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. --- Devon_gridded_RMSD_bedrock.tif :Root mean square deviation (RMDS) of the bedrock topography [m]. The RMSD was computed ...